Inhaled Corticosteroids in COPD: Determinants of Use and Trends in Patient Persistance with Treatment - Lucie Blais; Jean Bourbeau; Odile Dheehy; Jacques LeLorier (Canadian Respiratory Journal)
METHODS: The determinants of a new treatment with inhaled corticosteroids and secular trends in patient persistence with treatment among chronic obstructive pulmonary disease (COPD) patients were investigated. A cohort of 3768 physician-diagnosed, elderly COPD patients was selected between 1990 and 1996 from the health care administrative database of the Régie de l'assurance maladie du Québec. A nested case-control design was used to identify patient and physician characteristics that were associated with a new treatment with inhaled corticosteroids. Treatment persistence with inhaled corticosteroids was also estimated using Kaplan-Meier analysis. In addition to that, changes in treatment persistence over time, from 1990 to 1995, were investigated by estimating the yearly proportion of patients persisting for less than one year.